Sarcopenia and peripheral arterial disease: a systematic review. Issue 4 (10th July 2020) - Pizzimenti, Mégane; Meyer, Alain; Charles, Anne‐Laure; Giannini, Margherita; Chakfé, Nabil; Lejay, Anne; Geny, Bernard
Abstract: Background: Patients with lower extremity peripheral arterial disease (PAD) and sarcopenia are a population at risk requiring specific and targeted care. The aim of this review is to gather all relevant studies associating sarcopenia and PAD and to identify the underlying pathophysiological mechanisms as well as potential therapeutic strategies to improve skeletal muscle function. Methods: A systematic review was carried out following the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA). Results: Data extraction allowed the evaluation of 140 publications; 87 met the inclusion criteria; of which 79 were included in the final review, reporting sufficient data for epidemiological and diagnostic criteria, mechanical analysis, and therapeutic approaches. Epidemiological analysis and diagnostic criteria were based on 18 studies following 2362 PAD patients [31.39% (SD 7.61) women], aged 72.42 (SD 2.84); sarcopenia was present in 34.63% (SD 12.86) of the patients. Mechanical and pathway analysis were based on five animal studies and 29 clinical reports, showing significantly altered muscle strength and function in 1352 PAD patients [26.49% (SD 17.32) women], aged 67.67 (SD 5.14) years; impaired muscle histology in 192 PAD patients (9.2% (SD 11.22) women), aged 64.3 (SD 0.99) years; +58.63% (SD 25.48) of oxidative stress in 69 PAD patients [16.96% (SD 8.10) women], aged 63.17 (SD 1.43) years; mitochondriopathy in 153 PAD patients [29.39% (SD 28.27) women], aged 63.50 (SD 1.83) years; +15.58% (SD 7.41) of inflammation in 900 PAD patients [40.77% (SD 3.71) women], aged 74.88 (SD 2.76) years; and altered signalling pathways in 51 PAD patients [34.45% (SD 32.23) women], aged 72.25 (SD 5.25) years. Therapeutic approaches analysis was based on seven animal studies and 21 clinical reports. In total, 884 patients followed an exercise therapy, and 18 received an angiogenesis treatment; 30.84% (SD 17.74) were women. Mean ages of patients studied were 66.85 (SD 3.96). Conclusions: Sarcopenia and lower extremity PAD have musculoskeletal consequences that directly impair patients' quality of life and prognosis. Although PAD is primarily a vascular disease, all etiological factors of sarcopenia identified so far are present in PAD. Indeed, both sarcopenia and PAD are accompanied by oxidative stress, skeletal muscle mitochondrial impairments, inflammation, inhibition of specific pathways regulating muscle synthesis or protection (i.e. IGF‐1, RISK, and SAFE), and activation of molecules associated with muscle degradation. To date, besides revascularization, the best therapeutic strategy includes exercise, but approaches targeting the underlying mechanisms still deserve further studies.